SODplex, a Series of Hierarchical Multiplexed Real-Time PCR Assays for the Detection and Lineage Identification of Phytophthora ramorum, the Causal Agent of Sudden Oak Death and Sudden Larch Death - Arnaud Capron; Padmini Herath; D. I. Ojeda Alayon; Sandra Cervantes; Brittany Day; Avneet Brar; Guillaume J. Bilodeau; Simon F. Shamoun; Joan Webber; Clive Brasier; Nicolas Feau; Richard C. Hamelin (PhytoFrontiers, 2023)
Since its emergence in the 1990s, the invasive pathogen Phytophthora ramorum has spread in Europe and the west coast of North America, causing sudden oak death in the United States and sudden larch death in the United Kingdom, resulting in the mortality or destruction of millions of trees. Due to its invasive nature, its damage potential, its wide host range, and its ability to disseminate via the plant trade, P. ramorum has been placed on quarantine lists worldwide. Rapid and reliable detection of the pathogen and identification of its lineages are crucial to limit spread and inform mitigation and eradication efforts. SODplex, a suite of new multiplex real-time PCR tools, was developed to streamline the detection and identification of P. ramorum. It offers four multiplexed assays covering different use cases. SODplex-base combines primers and probes for the sensitive and accurate detection of Phytophthora spp. and P. ramorum. SODplex-ITS and SODplex-mito offer a single-step identification of P. ramorum and the EU1, NA1, and NA2 lineages present in the United States and Canada. SODplex-lin targets each of the four P. ramorum lineages present in Europe and North America in a single reaction. The assays have high levels of accuracy and are robust to the use of different instruments, different operators, and different temperatures. The redundancy within the assays reduces the likelihood of false negatives and false positives. The SODplex assays presented here improve the toolbox available for the detection of P. ramorum and its lineages. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.